Diverse diagnostic and management approaches for acute rheumatic fever in Australia and New Zealand: findings of a prospective clinical study - David Broadhurst; Bo Remenyi; Nigel J Wilson; Jonathan R Carapetis; Shirley Lawrence; Florina Chan Mow; Joshua Reginald Francis; Jennifer Yan; Anna P Ralph; Glenn Pearson; Mark Mayo; Rachel Webb; et al. (BMJ Open, 2025)
Objectives To describe diagnostic and management characteristics of acute rheumatic fever (ARF) among participants in the ‘Searching for a Technology-Driven Acute Rheumatic Fever Test’ study, in order to answer clinical questions and determine epidemiological and practice differences in different settings.Design Multisite, prospective cohort study.Setting One hospital in northern Australia and two hospitals in New Zealand, 2018–2021.Participants 143 episodes of definite, probable or possible ARF among 141 participants (median age 10 years, range 5–23; 98% Indigenous).Primary and secondary outcome measures Participant characteristics, clinical, biochemical and echocardiographic data were explored using descriptive data. Associations with length of stay were determined using multivariable regression analysis.Results ARF presentations were heterogeneous with the most common ARF ‘phenotype’ in 19% of cases being carditis with joint manifestations (polyarthritis, monarthritis or polyarthralgia), fever and PR prolongation. The total proportion of children with carditis was 61%. Australian compared with New Zealand participants more commonly had ARF recurrence (22% vs 0%), underlying RHD (48% vs 0%), possible/probable ARF (23% vs 9%) and were underweight (64% vs 16%). Erythrocyte sedimentation rate (ESR) provided an incremental diagnostic yield of 21% compared with C reactive protein. No instances of RHD were diagnosed among participants in New Zealand. Positive throat Group A Streptococcus culture was more common in New Zealand than in Australian participants (69% vs 3%). Children often required prolonged hospitalisation, with median hospital length-of-stay being 7 days (range 2–66). Significant predictors for length of stay in a multivariable regression model were valve disease (adjusted OR (aOR) 1.56, 95% CI 1.23 to 1.98, p<0.001), requirement for corticosteroids (aOR 1.99, 95% CI 1.22 to 3.26, p=0.007) and higher ESR (aOR 1.4, 95% CI 1.17 to 1.67, p<0.001).Conclusions This study provides new knowledge on ARF characteristics and management and highlights international variation in diagnostic and management practice. Differing approaches need to be aligned. Meanwhile, locally specific information can help guide patient expectations after ARF diagnosis.